Roofing sheets systems for industrial sheds for different wind zones based on static load testing - Narayanan, S.P. (Construction Research Institute of Malaysia, 2014)
Rooing sheets of industrial sheds have been observed to fail in uplift under extreme wind conditions as in a cyclone. This paper presents the results of static uplift load tests on asbestos cement and galvanized iron corrugated rooing sheet systems used in India using gravity load method. About 250 full-scale tests were carried out on rooing sheet systems with different connections for span/purlin spacing of 1.4 m. The ultimate loads obtained from the tests are used to evaluate the maximum permissible wind speeds. The values are compared with design wind speeds for critical and interior regions of the roof for different wind zones. The suitability of a particular rooing sheet system for a particular wind zone is then assessed. For Asbestos Cement rooing sheet system for both cases (as per IS 875 Part 3 1987 and modiied basic wind speed for zone 2) no suitable connections are available for standard span of 1.4 for zone 1 (both single span and double span). For zone 2 and 3 no suitable connections are available for single span case. For Corrugated Galvanised Iron rooing sheet of 0.6 mm thickness and standard span of 1.4 m suitable connections are available for wind zones 1 and 2. No suitable connections are available if modiied basic wind speeds are used for zone 2. Suitable shorter spans and connections have been identiied for these cases through static load testing.